Direct and indirect health economic impact of hypoglycaemia in a global population of patients with insulin-treated diabetes. (April 2018) - Aronson, Ronnie; Galstyan, Gagik; Goldfracht, Margalit; Al Sifri, Saud; Elliott, Lisa; Khunti, Kamlesh
Highlights: Insulin treatment of diabetes is compromised and more costly with hypoglycaemia. The HAT study investigated the direct and indirect economic costs of hypoglycaemia. Direct: increased glucose monitoring, hospitalisation and medical contact occurred. Indirect: work absence, or reduced punctuality were common, especially in T2D. Regional variations in impact were found, from both direct and indirect sources. Abstract: Aims: The Hypoglycaemia Assessment Tool (HAT) study investigated the health economic impact of hypoglycaemic events in 24 countries, including countries without previously published data on hypoglycaemia. Methods: Self-assessment questionnaires and patient diaries (4-week prospective period) were completed by adults with type 1 (T1D) or type 2 diabetes (T2D) treated with insulin for more than 12 months (N = 27, 585). Results: Direct economic impacts of hypoglycaemia during the 4-week prospective period, included increased blood glucose monitoring (reported by 69.7% [T1D] and 60.9% [T2D] of patients), hospitalisation (T1D 2.1%; T2D 3.4% of patients) and medical contact (clinic or telephone; T1D 3.8%; T2D 6.8% of patients). Regional variation in medical contact and hospitalisation was found, with the highest usage in Russia (T1D 17.1%; T2D 17.3%), and Latin America (T1D 5.2%; T2D 6.8%) respectively. Indirect economic impacts following hypoglycaemia included loss of productivity due to absence from work or study; 3.9% (T1D) and 6.2% (T2D) of patients. Regional differences in work productivity were noted among patients with T2D, with a low prevalence in Northern Europe and Canada (0.9%) and high in Southeast Asia (14.6%). Conclusions: This study shows that hypoglycaemia has a significant but variable impact on the economics of diabetes healthcare globally.